Program Upskilling dan Reskilling: Meningkatkan Kompetensi Guru MGMP Teknik Pemesinan Melalui Pelatihan CNC dan CAM di Era Revolusi Industri 4.0 - Febri Prasetya; Fiki Efendi; Budi Sayhri; Iqbal Parezi (PUSAKO : Jurnal Pengabdian Psikologi, 2026)
The rapid development of manufacturing technology in the era of the Industrial Revolution 4.0 requires continuous improvement of human resource competencies, particularly among vocational high school (SMK) teachers in the Machining Engineering field. However, limited facilities and insufficient access to training programs have resulted in many teachers lacking proficiency in Computer Numerical Control (CNC) and Computer-Aided Manufacturing (CAM) technologies. This Community Service Program (PkM) aimed to enhance the competencies of teachers from the Machining Engineering Teachers’ Association (MGMP) of West Sumatra through an upskilling and reskilling program focused on CNC machine operation and CAM software utilization. The program was conducted on September 28–29, 2024, at the CNC Laboratory of the Faculty of Engineering, Universitas Negeri Padang, involving 20 machining engineering teachers. A mixed-methods approach was employed, utilizing observations, interviews, and questionnaires for data collection. The training materials covered fundamental CNC concepts, MasterCAM software applications, toolpath configuration, program transfer procedures, and CNC machine operation. The results indicated that participants actively engaged in the training and demonstrated improvements in their knowledge and skills related to CAM-based CNC programming and operation. Evaluation results showed an average participant satisfaction score of 4.15, categorized as satisfactory. The highest-rated indicator in the training content aspect was participants’ ability to receive and understand the material (4.42), while in the training implementation aspect, the highest score was attributed to the organizers’ ability to create an engaging learning environment (4.66). In addition to improving teachers’ competencies, the program produced CAM-based learning media and job sheets that can be utilized in vocational school instruction. The program effectively supported the implementation of the Link and Match policy between vocational education and industry needs and contributed to improving the quality of machining engineering education in West Sumatra.